Hepatic steatosis detected by ultrasonography as a predictor of insulin resistance in obese patients - Isaksen, Victoria Therese (UiT Norges arktiske universitet, 2014)
Non-alcoholic fatty liver disease is closely related to the Metabolic syndrome. A significant feature of NAFLD is the presence of hepatic steatosis, which can be assessed by ultrasonography, by measuring the hepatorenal index (HRI), a comparison of liver and kidney acoustic echo densities. This study aims to investigate if HRI can predict insulin resistance. Ninety participants from the obesity clinic and the Sixth Tromsø Study were included. HOMA1-IR, body mass index and HRI were measured. ROC analyses were performed, detecting insulin resistance at HOMA1-IR values 2.3 or 2.5. Groups of participants with BMI ≥30 (n=46) and BMI ≥35 (n=27) were analysed specifically. Results: For BMI ≥30, HRI at level 1.11 had sensitivity=0.94 and specificity=0.54, and HRI=1.42 had sensitivity=0.33 and specificity=0.96. For BMI ≥35, HRI=1.17 had sensitivity=0.93 and specificity=0.77, whereas HRI= 1.42 had a sensitivity of 0.29 and a specificity of 0.92. (All test property values calculated for HOMA1-IR ≥2.3). Conclusion: Mild hepatic steatosis diagnosed by ultrasound is a good predictor for diagnosing insulin resistance, especially in obese patients.